Analysis of Trust in Serbia: Psychological and Sociological Implications - Drndarević, Nikola; Protić, Sonja (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
This study aimed to analyze social and institutional trust in Serbia and its demographic and socioeconomic correlates. Moreover, two alternative models on the direction of influence between social and institutional trust were tested. The European Social Survey data in the Serbian community sample (N = 1660, 49% women, mean age 52.5 years (SD = 17.7)) revealed generally low levels of all the aspects of trust, whereas trust in international institutions was the lowest. Participants who have lost a spouse or belonged to an older generation reported lower social trust and trust in international institutions, but higher trust in local institutions. Lower trust in local institutions but higher social trust was reported by participants with higher income and education. Model testing effects of social trust on institutional trust showed a better fit than the reversed model. These results indicate the continuity of the 1990s' trust crisis: the epistemic hypervigilance and system that cannot be trusted. Mediators of the relationship between social and institutional trust should be investigated in future research.